2006
DOI: 10.3201/eid1211.060542
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Avian Influenza A H5N1 in a Dog

Abstract: Avian influenza H5N1 virus is known to cross the species barrier and infect humans and felines. We report a fatal H5N1 infection in a dog following ingestion of an H5N1-infected duck during an outbreak in Thailand in 2004. With new reports of H5N1 virus continuing across Asia, Europe, and Africa, this finding highlights the need for monitoring of domestic animals during outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
170
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(183 citation statements)
references
References 12 publications
3
170
1
2
Order By: Relevance
“…HPAIV has also been detected in commercial frozen duck carcasses of retained slaughter batches (Harder et al, 2009), which has increased concern about the food safety of poultry products by its zoonotic implications. Similarly, the transmission of H5N1 HPAIV from infected carcasses to other animals in HPAIV-endemic areas has also been reported in different carnivores such as domestic cats (Songserm et al, 2006a) and dogs (Songserm et al, 2006b), tigers and leopards (Keawcharoen et al, 2004) and red foxes (Reperant et al, 2008). Nevertheless, kinetic and systematic studies on the persistence of AIV in different tissues from infected carcasses have not been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…HPAIV has also been detected in commercial frozen duck carcasses of retained slaughter batches (Harder et al, 2009), which has increased concern about the food safety of poultry products by its zoonotic implications. Similarly, the transmission of H5N1 HPAIV from infected carcasses to other animals in HPAIV-endemic areas has also been reported in different carnivores such as domestic cats (Songserm et al, 2006a) and dogs (Songserm et al, 2006b), tigers and leopards (Keawcharoen et al, 2004) and red foxes (Reperant et al, 2008). Nevertheless, kinetic and systematic studies on the persistence of AIV in different tissues from infected carcasses have not been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Dogs are susceptible to multiple IAV subtypes. H3N8, H3N2, H3N1, H5N1, H5N2 and H9N2 IAVs have been detected in dogs (Crawford et al, 2005;Songserm et al, 2006;Su et al, 2014a, b;X. Sun et al, 2013;Y.…”
Section: Introductionmentioning
confidence: 99%
“…1,25 A subsequent serosurvey 5 revealed that 25% of 629 asymptomatic dogs had been exposed to the virus in Thailand. The transmission of an entire avian FLUAV subtype H3N2 to dogs in South Korea was identified in 2007, 23 and additional studies 16,24 support the sustained transmission of this avianorigin H3N2 virus between South Korean dogs.…”
Section: Introductionmentioning
confidence: 99%